Juridical Analysis of the Influence of Technological Developments on the Crime of Sexual Violence by Children - Muskin, Rifdi Faris; Abe, Muhammad Faiz Nurifumi; Mahpud, Subhan Amrullah; Ismayana, Ismayana; Noupel, M. (Pelopor Publikasi Akademika, 2025)
This study aims to analyze the qualifications of transmitting electronic information and/or electronic documents with sexual content beyond the will of the recipient, aimed at sexual desire, in accordance with Article 14 paragraph (1) letter b of the TPKS Law and how to apply the Systematic Specialist Lex in Article 27 of the ITE Law and Article 14 of the TPKS Law. Normative legal research has the same definition as doctrinal research, which is research based on legal materials (library based), focusing on reading and studying primary and secondary legal materials. The crime of sexual violence against children is a criminal act that uses violence or threats of violence against children so that the child can be coerced into having sexual relations. In general, there are two factors that cause sexual violence, namely internal factors and external factors. Internal factors include the proximity of the perpetrator to the victim, the role of the perpetrator, and the position of the victim. External factors consist of environmental influences, such as being far from crowds, loneliness, or enclosed places that allow perpetrators to commit sexual violence.